Piperazine-Derived α1D/1A Antagonist 1- Benzyl-N- (3-(4- (2-Methoxyphenyl) Piperazine-1-yl) Propyl) -1H- Indole-2- Carboxamide Induces Apoptosis in Benign Prostatic Hyperplasia Independently of α1-Adrenoceptor Blocking - Xiao, Qing; Liu, Qi-Meng; Jiang, Ru-Chao; Chen, Kai-Feng; Zhu, Xiang; Ma, Lei; Li, Wei-Xi; He, Fei; Huang, Jun-Jun (Frontiers in Pharmacology, 2021)
revious studies have indicated that α1D/1A antagonist naftopidil (NAF) suppresses prostate growth by decreasing cell proliferation without affecting apoptosis and prostate volume in benign prostatic hyperplasia (BPH). A NAF-derived α1D/1A antagonist 1- benzyl-N-(3-(4-(2-methoxyphenyl) piperazine-1-yl) propyl)-1H-indole-2- carboxamide (HJZ-12) has been reported from our laboratory, which exhibits high subtype-selectivity to both a1D- and a1A- AR (47.9- and 19.1- fold, respectively) with respect to a1B-AR in vitro. However, no further study was conducted. In the present study, a pharmacological evaluation of HJZ-12 in BPH was performed on an estrogen/androgen-induced rat BPH model and human BPH-1 cell line. In vivo, HJZ-12 exhibited better performance than NAF in preventing the progression of rat prostatic hyperplasia by not only decreasing prostate weight and proliferation (similar to NAF) but also, shrinking prostate volume and inducing prostate apoptosis (different from NAF). In vitro, HJZ-12 exhibited significant cell viability inhibition and apoptotic induction in BPH-1 cell line, without presenting cell anti-proliferation properties. Intriguingly, the role of HJZ-12 on cell viability and apoptosis was an α1-independent action. Furthermore, RNA-Seq analysis was applied to screen out six anti-apoptotic genes (Bcl-3, B-lymphoma Mo-MLV insertion region 1 [Bmi-1], ITGA2, FGFR3, RRS1, and SGK1). Amongst them, Bmi-1 was involved in the apoptotic induction of HJZ-12 in BPH-1. Overall, HJZ-12 played a remarkable role in preventing the progression of prostatic hyperplasia through α1-independent apoptotic induction, indicating that it will be a multi-target effective candidate for BPH treatment.